Agricultural Commodity Supply Response - Gede Mekse Korri Arisena; Henita Fajar Oktavia (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2020)
Creating a farmer who able to actively respond to the agricultural commodity supply is a major challenge faced by the national government today. A dominant supply response to a certain factor would be easier to be identified by the stakeholder to arrange policies in improving the volume of agricultural commodity production. This study aimed to: 1) summarize the theories and study results about the supply demands, 2) analyze the factors that affected the supply response, and 3) examine the common problem-solving method used to analyze the supply response method. The secondary data was employed in this study by collecting relevant studies and theories. A review then conducted to address the study aims. Results showed that the farmer supply response to several factors was required to utilize the superior agricultural and horticulture (fresh fruit) commodity opportunities in competing on the world market. Vietnam, Thailand, and Latin America also strictly competing in exporting their commodity, but Indonesian healthy products were having a great chance to win this competition.